Determinan Kunjungan Balita ke Posyandu di Wilayah Kerja Puskesmas Tagolu Kabupaten Poso - Dewi Ningsih Noeralim; Budiman Budiman; Finta Amalinda (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Toddler visits to Integrated Health Posts are an important indicator for continuous monitoring of child growth, development, nutritional status, and health. Low attendance may delay the detection of nutritional problems and growth disorders. This study aimed to identify the determinants of toddler visits to Integrated Health Posts in the working area of Tagolu Community Health Center, Poso Regency. This study used a quantitative approach with an observational analytic design and a cross sectional study design. The population consisted of mothers with toddlers aged 0 to 59 months in the working area of Tagolu Community Health Center. A total of 97 respondents were selected using proportional random sampling. The independent variables were maternal knowledge, maternal attitude, role of cadres, and distance to the Integrated Health Post, while the dependent variable was toddler visits to the Integrated Health Post. Data were analyzed using the chi square test and logistic regression. The results showed that maternal knowledge was associated with toddler visits to the Integrated Health Post with a p value of 0.007, maternal attitude with a p value of 0.011, role of cadres with a p value of 0.011, and distance with a p value of 0.011. Multivariate analysis showed that distance was the most dominant determinant, with B 3.200, Sig. 0.001, and Exp (B) 24.541. This study concludes that knowledge, attitude, role of cadres, and distance are associated with toddler visits to Integrated Health Posts, with distance being the most dominant factor. The Community Health Center needs to strengthen maternal education, cadre roles, and service strategies that are more accessible to families with toddlers.